Development of an American Indian Diabetes Education Cultural Supplement: A Qualitative Approach - Wilson, Jamie; Thomson, Cynthia; Sabo, Samantha; Edleman, Anathea; Kahn-John, Michelle (Frontiers in Public Health, 2022)
Objective The purpose of this study was to culturally enhance a diabetes education program for Diné (Navajo) community members with Type 2 diabetes. Though the recommendation to culturally adapt health education curricula was meant to improve health education for American Indians and Alaskan Natives (AIANs), it has inadvertently created a “one size fits all” approach. This approach does not properly address the need for tribe-specific cultural health messaging, defined as incorporating cultural elements deemed relevant to the population. Tribe-specific health information and programming, such as integrating Diné worldviews and Indigenous knowledge among Diné people as described here, are essential to creating a culturally relevant and effective and meaningful approach to disease self-management. Methods A conversation guide, based on the Hózhó Resilience Model—a Diné framework on healthy living, was used to engage key cultural experts in interviews about traditional stories and teachings regarding health and wellness. Three specific self-care behaviors relevant to Type 2 diabetes self-management were discussed: (1) healthy eating, (2) physical activity, and (3) healthy coping. Interviews were audio-recorded, transcribed and analyzed using a qualitative thematic analysis method. Results Diné healers and cultural experts informed the development of an educational tool called Diné Health. Key themes that emerged from the data included the importance of discipline, positivity and mindfulness in the context of Hózhó. Conclusion Culturally safe and meaningful engagement with cultural leaders and the use of qualitative research methods can inform deep-level cultural adaptations essential to developing tribe-specific diabetes education programs. The approaches used here can guide the development, implementation, and testing of culturally-informed health education for AIAN populations.